Tocilizumab-Induced Acute Liver Injury in Adult Onset Still’s Disease - Michael Drepper; Laura Rubbia-Brandt; Laurent Spahr (Case Reports in Hepatology)
Background. Tocilizumab, a monoclonal humanized anti-IL-6 receptor antibody, is used in treatment of refractory adult onset Still’s disease (AOSD). Mild to moderate liver enzyme elevation is a well-known side effect, but severe liver injury has only been reported in 3 cases in the literature. Case. A young female suffering from corticoid and methotrexate refractory AOSD was treated by tocilizumab. After 19 months of consecutive treatment, she developed acute severe liver injury. Liver biopsy showed extensive hepatocellular necrosis with ballooned hepatocytes, highly suggestive of drug-induced liver injury. No other relevant drug exposure beside tocilizumab was recorded. She recovered totally after treatment discontinuation and an initial 3-day course of intravenous N-acetylcysteine with normalization of liver function tests after 6 weeks. Conclusion. Acute severe hepatitis can be associated with tocilizumab as documented in this case. Careful monitoring of liver function tests is warranted during tocilizumab treatment.